Musa paradisica peel extract as green corrosion inhibitor for mild steel in HCl solution - Ji G.; Anjum S.; Sundaram S.; Prakash R. (My University, 2025)
The inhibition and adsorption effects of the aqueous extracts of Musa paradisica (Banana) peels on mild steel corrosion in 1. M HCl as well as change in inhibition efficiency with ripening of the peels are investigated by weight loss measurement, electrochemical impedance spectroscopy (EIS), Tafel polarization and atomic force microscopy (AFM) techniques. Inhibition ability of the extracts decreases with the maturity stages. Furthermore, the extracts are characterized by FTIR spectroscopy, UV-visible spectroscopy and high performance liquid chromatography (HPLC) techniques. Adsorption behavior of the extracts is also studied, which suggest Langmuir isotherm model as a most suitable adsorption mechanism. © 2014 Elsevier Ltd.